Pengaruh Kreativitas terhadap hubungan Kepuasan Kerja dan Kinerja Karyawan pada Koperasi di Kecamatan Denpasar Utara - Nyoman Resa Adhika; Putu Pradiva Putra Salain; Ni Made Dwi Puspitawati; Putu Agus Eka Rismawan; I Gede Rihayana; I Made Risma M Arsha (UNHI Press, 2022)
Maximum cooperative management has an impact on cooperative performance that is getting better and healthier. Management of human resources in cooperatives is a way to improve cooperative performance. From the development of cooperatives and the results of interviews with cooperative employees about creativity that tends to be low, job satisfaction is lacking and employee performance is low, it will be very important and it is necessary to do research. Research respondents totaled 60 people, with a sampling technique that is non-probability sampling and analyzed using Smart PLS. The results and discussion of the data in this study indicate that the performance of employees at cooperative institutions in the North Denpasar sub-district is strongly influenced by the level of creativity and the role of employee job satisfaction itself. From these results, it is suggested that cooperative institutions in developing their businesses should be based on the value of creativity in providing services to the community, considering that cooperative institutions currently have almost the same service concept so they need to be supported by a dimension of creativity that provides innovation value in competition.